2020
DOI: 10.3390/jcm9082642
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of RAS, PIK3CA, and PTEN Mutations in Non-Small Cell Lung Cancer Using Cell-Free DNA

Abstract: Mutations in the EGFR gene downstream signaling pathways may cause receptor-independent pathway activation, making tumors unresponsive to EGFR inhibitors. However, the clinical significance of RAS, PIK3CA or PTEN mutations in NSCLC is unclear. In this study, patients who were initially diagnosed with NSCLC or experienced recurrence after surgical resection were enrolled, and blood samples was collected. Ultra-deep sequencing analysis of cfDNA using Ion AmpliSeq Cancer Hotspot Panel v2 with Proton platforms was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“… 18 Wang et al showed that PIK3CA mutations are related to OS and PFS, 3 affect EGFR-TKI sensitivity, and have a poor prognosis. Chang et al 19 reported that patients treated with a EGFG-TKI without RAS/PIK3CA/PTEN mutations had a mPFS of 15.1 months and OS of 53.8 months, but for patients with RAS/PIK3CA/PTEN mutations the mPFS was only 19.9 months and OS was only 27.4 months.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Wang et al showed that PIK3CA mutations are related to OS and PFS, 3 affect EGFR-TKI sensitivity, and have a poor prognosis. Chang et al 19 reported that patients treated with a EGFG-TKI without RAS/PIK3CA/PTEN mutations had a mPFS of 15.1 months and OS of 53.8 months, but for patients with RAS/PIK3CA/PTEN mutations the mPFS was only 19.9 months and OS was only 27.4 months.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR activation promotes tumor growth, invasion and migration via the PIK3CA and mTOR pathways. PIK3CA mutations may cause resistance to EGFR -targeting therapies in patients with lung cancer ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…PTEN is one of the most commonly inactivated tumor suppressor genes in a wide variety of cancer types. PTEN loss and the activation of PI3K/mTOR signaling are associated with EGFR TKIs resistance in patients with NSCLC ( 20 , 21 ). PTEN mutations were observed in the breast (4.4%) and lung (6%) groups.…”
Section: Discussionmentioning
confidence: 99%